Unlike Catalyzing Error-Free Bypass of 8-oxodGuo, DNA Polymerase λ Is Responsible for a Significant Part of Fapy•dG-Induced G→T Mutations in Human Cells - Pande, Paritosh (Biochemistry, 2015)
8-OxodGuo and Fapy•dG induced 10–22% mutations, predominantly G→T transversions, in HEK 293T cells in four TG*N sequence contexts, where N = C, G, A, or T. siRNA knockdown of pol λ resulted in a 34% and 55% increase in mutations in the progeny from the 8-oxodGuo construct in the TG*T and TG*G sequence, respectively, suggesting that pol λ is involved in error-free bypass of 8-oxodGuo. For Fapy•dG, in contrast, G→T mutations were reduced by 27% and 46%, respectively, in the TG*T and TG*G sequence, suggesting that pol λ is responsible for a significant fraction of Fapy•dG-induced G→T mutations.